PENDETEKSI KONSENTRASI GAS AMMONIA (NH3) BERBASIS INTERNET OF THINK - Rouhillah; Inzar Salfikar (Politeknik Aceh, 2021)
Everyone really needs air in the process of breathing, but they don't know how much ammonia (NH3) is in the air. Therefore it is necessary to monitor ammonia (NH3) levels in the room with an Internet of Think (IoT) based ammonia (NH3) concentration meter with Wemos D1 as a microcontroller and an MQ-137 sensor, with this measuring instrument you can find out the level of ammonia levels ( NH3) in the room in real time using the MQ-137 as an ammonia level sensor (NH3), a programmed Wemos D1 that can process the level of ammonia (NH3) levels in the air. From the experimental results that the MQ 137 sensor can be said to be linear because it gets the results of R2 = 0.9613216, the ammonia gas condition is more than 25 ppm, the buzzer and fan will turn on.